Functional human artificial chromosomes are generated and stably maintained in human embryonic stem cells. - Mandegar, M; Moralli, D; Khoja, S; Cowley, S; Chan, D; Yusuf, M; Mukherjee, S; Blundell, M; Volpi, E; Thrasher, A; James, W; Monaco, Z (2011)
We present a novel and efficient non-integrating gene expression system in human embryonic stem cells (hESc) utilizing human artificial chromosomes (HAC), which behave as autonomous endogenous host chromosomes and segregate correctly during cell division. HAC are important vectors for investigating the organization and structure of the kinetochore, and gene complementation. HAC have so far been obtained in immortalized or tumour-derived cell lines, but never in stem cells, thus limiting their potential therapeutic application. In this work, we modified the herpes simplex virus type 1 amplicon system for efficient transfer of HAC DNA into two hESc. The deriving stable clones generated green fluorescent protein gene-expressing HAC at high frequency, which were stably maintained without selection for 3 months. Importantly, no integration of the HAC DNA was observed in the hESc lines, compared with the fibrosarcoma-derived control cells, where the exogenous DNA frequently integrated in the host genome. The hESc retained pluripotency, differentiation and teratoma formation capabilities. This is the first report of successfully generating gene expressing de novo HAC in hESc, and is a significant step towards the genetic manipulation of stem cells and potential therapeutic applications.